Synthesis of branched 9-[2-(2-phosphonoethoxy)ethyl]purines as a new class of acyclic nucleoside phosphonates which inhibit Plasmodium falciparum hypoxanthine-guanine-xanthine phosphoribosyltransferase - Hocková, Dana; Holý, Antonín; Masojídková, Milena; Keough, Dianne T; de Jersey, John; Guddat, Luke W (Bioorganic & medicinal chemistry, 2009)
The malarial parasite Plasmodium falciparum (Pf) lacks the de novo pathway and relies on the salvage enzyme, hypoxanthine-guanine-xanthine phosphoribosyltransferase (HGXPRT), for the synthesis of the 6-oxopurine nucleoside monophosphates. Specific acyclic nucleoside phosphonates (ANPs) inhibit PfHGXPRT and possess anti-plasmodial activity. Two series of novel branched ANPs derived from 9-[2-(2-phosphonoethoxy)ethyl]purines were synthesized to investigate their inhibition of PfHGXPRT and human HGPRT. The best inhibitor of PfHGXPRT has a K(i) of 1 microM. The data showed that both the position and nature of the hydrophobic substituent change the potency and selectivity of the ANPs.
Keywords: Pentosyltransferases; Catalytic Domain; Humans; organofosfonáty; Computer Simulation; Purines; lidé; pentosyltransferasy; zvířata; Antimalarials; Drug Design; počítačová simulace; katalytická doména; puriny; racionální návrh léčiv; inhibitory enzymů; Organophosphonates; Animals; Plasmodium falciparum; Enzyme Inhibitors; antimalarika